Understanding the paradigma of opportunistic screening - Güldoğan, Nilgün; Daldal, İlke and Soyder, Aykut and Yılmaz, Ebru and Arslan, Aydan (The European Research Journal, 2022)
Objectives: To provide demographical and pathological characteristics of breast cancer patients diagnosed in a tertiary clinic with opportunistic screening and diagnostic workup and compare the results with the available national and global breast cancer statistics. Methods: Clinical and pathological data of breast cancer patients diagnosed in our tertiary breast clinic between March 14, 2017 and February 28, 2020 have been entered into a database and analyzed retrospectively. Results were analyzed and compared with the national and global statistics. Results: The total number of patients included in this study were 137 and the number of tumors was 145. Sixty-four (46.7%) patients were detected in screening. All of the patients were female. The mean age was 51.8 years. Eighteen (13.1%) patients were young females (< 40 years), 55 (40.1%) were in 40-49 years, 26 (18.9%) in 50-59 years, 24 (17.5%) in > 60-69 years, 14 (10.2%) in > 70 years. Of the invasive cancers, 100 (79.4%) were invasive ductal, 15 (11.9%) invasive lobular, 6 (4.8%) pleomorphic lobular, 4 (3.2%) papillary, and 1 (0.8%) tubular cancer. Distribution of stages were: 13.1% stage 0, 38.6% stage I, 29.6% stage II, 10.3% stage III, and 8.2% stage IV. The mean tumor diameter was 26.6 mm. Estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor-2 (HER-2) were positive in 82.5%, 61.9% and 15.8% of the tumors respectively. Conclusions: Results of this study are in accordance with the latest results of the National Breast cancer database, a project governed by the Turkish Federation of Breast Disease Societies (TMHDF), considering the tumor size, age distribution, histologic subtype analysis, receptor status. However, the percentage of early-stage tumors was higher in this study.